Genetic Variants in the Wnt Signaling Pathway Are Not Associated with Survival Outcome of Non-Small Cell Lung Cancer in a Korean Population - Yoo, Seung Soo; Hong, Mi Jeong; Choi, Jin Eun; Lee, Jang Hyuck; Baek, Sun Ah; Lee, Won Kee; Lee, So Yeon; Lee, Shin Yup; Lee, Jaehee; Cha, Seung Ick; Kim, Chang Ho; Cho, Sukki; et al. (Journal of Korean medical science, 2016)
Recently, genetic variants in the WNT signaling pathway have been reported to affect the survival outcome of Caucasian patients with early stage non-small cell lung cancer (NSCLC). We therefore attempted to determine whether these same WNT signaling pathway gene variants had similar impacts on the survival outcome of NSCLC patients in a Korean population. A total of 761 patients with stages I-IIIA NSCLC were enrolled in this study. Eight variants of WNT pathway genes were genotyped and their association with overall survival and disease-free survival were analyzed. None of the eight variants were significantly associated with overall survival or disease-free survival. There were no differences in survival outcome after stratifying the subjects according to age, gender, smoking status, and histological type. These results suggest that genetic variants in the WNT signaling pathway may not affect the survival outcome of NSCLC in a Korean population.